Juridical Review Of The Role Of Judges In Legal Discovery (Rechtvinding) According To The Principles Of Good Justice In Handling Cases (Civil) - Widi Okta Pratama; Dwi Putra Jaya; Ana Tasi Pase (JURNAL HUKUM SEHASEN, 2024)
Judges in examining and adjudicating cases, face a fact, that the written law is not always able to solve the problems faced, considering that the codification of the law, although it seems complete, is never perfect, because thousands of unexpected problems will be submitted to the judge. The purpose of this research is to find out the legal discoveries made by the settlement of cases (Civil). The research method used is normative legal research in the form of library research which is carried out by collecting legal materials both primary, secondary and or tertiary. The results of the research and discussion show that the umbrella for judges in making legal discoveries has been regulated in Indonesian positive law, namely that judges are independent and independent, may not refuse to hear, and must make legal considerations for decisions by mentioning articles of legislation or unwritten law as the basis for judging, by applying the meaning of judging according to the law by not discriminating against people so that civil case decisions are produced in accordance with legal values and a sense of justice that lives in society. In order to produce a civil decision, the judge must rely on the evidence submitted by the parties to the dispute, because the truth sought in a civil case is the formal truth, namely the truth that is born on the basis of formal evidence from the parties to the dispute.